Evaluation of an adult food literacy program - Begley, Andrea; Dhaliwal, Satvinder (2019)
Food literacy programs aim to improve planning, selection, preparation and eating of healthy foods. Governments are investing in these programs to improve dietary intakes at a population level. There are evaluation challenges in the design, methods and interpretation of results as these programs are not research trials. Food Sensations® for Adults (FSA) is a free four-week nutrition and cooking program funded by the Western Australia Department of Health targeted at low to middle income participants who would like to improve their food literacy. The aim of this research was to assess the effectiveness of FSA in improving the food literacy and other selected dietary behaviours. Methods used were to examine the mean self-reported change in participants using factor scores and to use tertile stratification to calculate change in those with low food literacy at the start of the program. Pre and post questionnaires were developed from validated tools and surveys. Statistical analysis identified a mean increase in post program scores for domains of Planning (9.7%), Selection (25.1%) and Preparation (11.9%)(p<0.001) (n=1092). There was a significant increase in self-reported fruit (¼ serve per day) and vegetables (½ serve per day) (p<0.0001). Of those classified with low food literacy, 61% significantly improved post-program scores for Planning, 74% for Selection and 65% for Preparation. FSA is effective in improving food literacy and dietary behaviours and these results add to the evidence base as to the level of effectiveness of these programs and for whom they might need to be targeted at in the future.